Production Efficiency Analysis in Egg Production in Khorasan Razavi Province, Iran: An Application of the Transcendental Frontier Model - Mohaddes, Seyed Ahmad (International Journal of Poultry Science, 2011)
The objective of this study is to determine the production efficiency of egg production in Khorasan Razavi. A cross-sectional data collected from 47 farms in the Khorasan province, as well as secondary data from the Iranian Statistical Year Book, were used to estimate production functions. The analysis was carried in three stages. In the first stage, the Transcendental and Cobb-Douglas production functions were estimated using OLS method. It was found that the transcendental production fit the data better than the Cobb-Douglas production function. The result showed that feed, pullet and cost of Energy inputs are the important factors in egg production. The second stage of the analysis estimated a Transcendental Stochastic production frontier model. The mean Technical, Allocation and Economic efficiency indices were 0. 92, 0.92 and 0.85 respectively. The results showed that farmers did not have major inefficiency in egg production with this current technology and should improve it for increasing production.